Heterogeneity of nitrogen fixation in the mesopelagic zone of the South China Sea - Wu, Siqi; Wan, Xianhui Sean; Du, Moge; Chen, Xirong; Selden, Corday R.; Benavides, Mar; Bonnet, Sophie; Löscher, Carolin R.; Hamersley, M. Robert; Mulholland, Margaret R.; Yan, Xiuli; Kao, Shuh-Ji (Frontiers in Marine Science, 2024)
Biological dinitrogen (N2) fixation, the energetically expensive conversion of N2 gas to ammonia, plays an essential role in balancing the nitrogen budget in the ocean. Accumulating studies show detectable N2 fixation rates below the euphotic zone in various marine systems, revealing new insights of marine N2 fixation. However, the reported rates are highly variable and frequently fall close to detection limits, raising the question of the ubiquity and significance of N2 fixation in the global dark ocean. Using highly sensitive isotopic labeling incubation including a set of control incubations, we confirm the occurrence of mesopelagic N2 fixation in the South China Sea. Interestingly, we consistently observed that ca. 30% of samples show a significant elevation of 15N in the particulate nitrogen after incubation at most depths (200 - 1000 m). Although this approach does not allow accurate quantification of N2 fixation rates, our data suggest the occurrence of dark N2 fixation yet with highly heterogeneous signals in the mesopelagic zone of the South China Sea. A data compilation of reported N2 fixation in the global dark ocean further reveals that such heterogeneity has also been observed elsewhere, unveiling the ubiquitous heterogeneity in mesopelagic N2 fixation. Thus, we call for more observations to constrain mesopelagic N2 fixation budgets and to understand the underlying mechanism for such heterogeneity.